Integration of AI and OR Techniques in Constraint Programming : 12th International Conference, CPAIOR 2015, Barcelona, Spain, May 18-22, 2015, Proceedings - Michel, Laurent; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book constitutes the proceedings of the 12th International Conference on the Integration of Artificial Intelligence (AI) and Operations Research (OR) Techniques in Constraint Programming, CPAIOR 2015, held in Barcelona, Spain, in May 2015. The 29 papers presented together with 8 short papers in this volume were carefully reviewed and selected from 90 submissions. The purpose of the conference series is to bring together researchers in the fields of Constraint Programming, Artificial Intelligence and Operations Research to explore ways of solving hard and large scale combinatorial optimization problems that emerge in various industrial domains. Pooling the skills and strengths of this diverse group of researchers has proved extremely effective and valuable during the past decade leading to improvements and cross-fertilization between the three fields as well as breakthrough for actual applications.
Keywords: Electronic data processing; Computer science; Computational complexity; Computer software; Artificial intelligence; Numeric Computing; Math Applications in Computer Science; Discrete Mathematics in Computer Science; Algorithm Analysis and Problem Complexity; Artificial Intelligence; Operations Research, Management Science